2012
DOI: 10.1073/pnas.1206378109
|View full text |Cite
|
Sign up to set email alerts
|

Linking habitat mosaics and connectivity in a coral reef seascape

Abstract: Tropical marine ecosystems are under mounting anthropogenic pressure from overfishing and habitat destruction, leading to declines in their structure and function on a global scale. Although maintaining connectivity among habitats within a seascape is necessary for preserving population resistance and resilience, quantifying movements of individuals within seascapes remains challenging. Traditional methods of identifying and valuing potential coral reef fish nursery habitats are indirect, often relying on visu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
64
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(65 citation statements)
references
References 33 publications
0
64
0
1
Order By: Relevance
“…Whereas larval and juvenile fishes often migrate great distances from the reefs they originated in (e.g. Palumbi 2003, McMahon et al 2012, it is believed that the home range of the adults of these species is limited (Zeller et al 2003). Although many reef species generally do not exceed a range of hundreds of meters from their home reefs, tagged individuals have been observed moving across much greater distances, occasionally in excess of several kilometers.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas larval and juvenile fishes often migrate great distances from the reefs they originated in (e.g. Palumbi 2003, McMahon et al 2012, it is believed that the home range of the adults of these species is limited (Zeller et al 2003). Although many reef species generally do not exceed a range of hundreds of meters from their home reefs, tagged individuals have been observed moving across much greater distances, occasionally in excess of several kilometers.…”
Section: Discussionmentioning
confidence: 99%
“…However, further research is needed to determine whether the observed increase in reliance on water column production for fishes on oceanic reefs reflected a dietary switch to a more phytoplanktonbased food web or an increase in the flow of phytoplankton C through the same food webs as on shelf reefs. While our study targeted adult individuals across the entire seascape, previous work has shown that ontogenetic shifts in habitat usage of coral reef fishes can also result in dramatic changes in resource utilization through time and space (Cocheret de la Moriniere et al 2003;McMahon et al 2012). …”
Section: S T E G a S T E S N I G R I C A N S C H A E T O D O N T R I mentioning
confidence: 99%
“…Given a lack of such management in most of the Red Sea, future connectivity research should focus on elucidating general patterns of larval dispersal, gene flow among populations, and linkages among the many types of coastal habitats found in the Red Sea (e.g., snapper migration corridors from coastal wetlands to reefs further offshore; McMahon et al 2012). Such data would be essential to inform the design of marine protected areas, should there be a move to develop them within this region.…”
Section: Connectivitymentioning
confidence: 99%